2016
DOI: 10.1177/0269881116677852
|View full text |Cite
|
Sign up to set email alerts
|

Set and setting, psychedelics and the placebo response: An extra-pharmacological perspective on psychopharmacology

Abstract: Placebo response theory and set and setting theory are two fields which examine how non-biological factors shape the response to therapy. Both consider factors such as expectancy, preparation and beliefs to be crucial for understanding the extra-pharmacological processes which shape the response to drugs. Yet there are also fundamental differences between the two theories. Set and setting concerns itself with response to psychoactive drugs only; placebo theory relates to all therapeutic interventions. Placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
275
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(290 citation statements)
references
References 96 publications
(115 reference statements)
12
275
0
3
Order By: Relevance
“…Changes in the ratings of subjective measures that were observed in the present study are not necessarily related to a pharmacological effect of 5-MeO-DMT, but could have resulted from uncontrolled variables such as response expectancy of the participants prior to and after the session or the set and setting of drug administration (Carhart-Harris et al 2018;Hartogsohn 2016). Yet, the finding that the strength of actual psychedelic experience was positively correlated to changes in non-judgment and negatively correlated with symptoms of depression, stress and anxiety strongly suggest that the inhalation of 5-MeO-DMT contributed to changes in these subjective measures.…”
Section: Discussionmentioning
confidence: 68%
“…Changes in the ratings of subjective measures that were observed in the present study are not necessarily related to a pharmacological effect of 5-MeO-DMT, but could have resulted from uncontrolled variables such as response expectancy of the participants prior to and after the session or the set and setting of drug administration (Carhart-Harris et al 2018;Hartogsohn 2016). Yet, the finding that the strength of actual psychedelic experience was positively correlated to changes in non-judgment and negatively correlated with symptoms of depression, stress and anxiety strongly suggest that the inhalation of 5-MeO-DMT contributed to changes in these subjective measures.…”
Section: Discussionmentioning
confidence: 68%
“…Personality has previously been associated with response to psychedelics (Studerus et al, 2012; Hartogsohn, 2016; Barrett et al, 2017). For example, trait ‘absorption’ has been shown to be predictive of sensitivity to psychedelics (Studerus et al, 2012), and the same has also been shown in relation to the intensity of ‘actual’ NDEs (Twemlow and Gabbard, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…One possible interpretation of these results is that participants felt more fatigued by the setting of the study under the influence of LSD, as they were sitting in their beds the whole day. Supporting this interpretation, a review of historical LSD research indicates that study results appear to be highly influenced by the setting of the study (Hartogsohn 2016), and recent research has shown heightened suggestibility under the drug (Carhart- Harris et al 2015) that may enhance the suggestion of "feeling sleepy" as the participants were confined to a bed throughout the day. Furthermore, the increase in vigilance reduction was not observed in participants in Bershad et al (2019), discussed below.…”
Section: Discussionmentioning
confidence: 99%